Efeitos da adenosina em arritmias induzidas por Ouabaína - Fogaca, Rosalvo Tadeu Hochmulller (1987)
Adenosine, an endogenous nucleoside is known to alter some of the electrophysiological properties of the heart. Liberated in large quantities through ischamic myocardium, it seems to be alter arrhythmogenic processes of this organ. In the present work, we have investigated the effects as well as the mechanisms of action of this substance in ouabain-induced arrhythmias. The experiments were carried out in guinea pig and toad hearts using "in vivo" and "in vitro" models. In "in vivo" experiments, intravenous infusion of _2 adenosine (Q.02 ml/min. of saline containing 1 x 10 M) elevated the dose of ouabain (intermittent administration of 4 ug every 2 min.) necessary to produce first extrasystole from 69.8 to 95.3 y.g/kg body weight (p < 0.01). In isolated guinea pig hearts perfused with adenosine -5 -6 (1 x 10 M) and ouabain (3.3 x 10 M) combination, there was a reduction in the arrhythmias in relation to those exposed to ouabain alone, as evidenced by decreased incidence of extra-systoles, tachycardia and cardiac blockade irrespective of ventricular fibrillation. This reduction was more prominent in hearts in which atria were excised. In isolated heart preparations stimulated at a frequency of 4.5 a 5.0 Hz, perfusion with adenosine (1 x -5 10 M) alone promoted a significant increase in the period of oyerdrive suppressiqn cqmpared tq those perfused with ouabain. Adenosine did not alter the contractile responses of guinea pig auticular strips and toad ventricular promoted by a reduction in extracellular sodium in the presence of caffeine (5 x 10~3M). In Purkinje cells of guinea pig heart, adenosine partly recerved ouabain-induced depolarization. The results of this study demonstrate that adenosine may have a protective function against ouabain-induced cardiac arrythimias. Two mechanisms seem to have effective participation in the cardiac protection offered by adenosine: 1) a reduction in cardiac frequency and 2) a hyperpolarizing effect on Purkinje fibers.